2023
DOI: 10.1097/hjh.0000000000003560
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effect of systemic immune inflammatory index on hypertension in American adults (NHANES 2017–2020)

Yumeng Shi,
Wei Zhou

Abstract: Background and aims: Research reports on the relationship between systemic immune-inflammation index (SII) and hypertension are limited. We aim to evaluate the possible relationship between SII and hypertension. Methods and results: We conducted a cross-sectional analysis of adults from the National Nutrition and Health Database from 2017 to 2020. In this study, 13 742 participants were included. The exposure variable in this study was the systemic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, in the clinical practice of using 5-FU, it is necessary to closely monitor the inflammatory status of patients in order to enable early prevention, monitoring, and management of cardiotoxicity related to 5-FU, especially when monocyte levels are low (T1:M ≤ 0.38 × 10 9 /L). A recent study has confirmed the close association between SII levels and the development of cardiovascular diseases, including hypertension, heart failure, and acute myocardial infarction [ 33 35 ]. In a meta-analysis conducted by Ye et al in 2022, which encompassed 152,996 patients across 13 studies, it was observed that elevated SII levels were linked to an increased risk of cardiovascular diseases such as ischemic stroke, hemorrhagic stroke, and myocardial infarction [ 36 ].…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, in the clinical practice of using 5-FU, it is necessary to closely monitor the inflammatory status of patients in order to enable early prevention, monitoring, and management of cardiotoxicity related to 5-FU, especially when monocyte levels are low (T1:M ≤ 0.38 × 10 9 /L). A recent study has confirmed the close association between SII levels and the development of cardiovascular diseases, including hypertension, heart failure, and acute myocardial infarction [ 33 35 ]. In a meta-analysis conducted by Ye et al in 2022, which encompassed 152,996 patients across 13 studies, it was observed that elevated SII levels were linked to an increased risk of cardiovascular diseases such as ischemic stroke, hemorrhagic stroke, and myocardial infarction [ 36 ].…”
Section: Discussionmentioning
confidence: 90%
“…The present study found a relationship between SII and hypertension aligning with prior research. [28–30] Three NHANES studies confirmed a positive relationship between SII and blood pressure. [28–30] In an NHANES examination of metabolic syndrome and SII, elevated blood pressure was significantly and positively linked with SII.…”
Section: Discussionmentioning
confidence: 99%
“…SII has been examined for its association with hypertension or blood pressure in several cross-sectional studies using data from the United States National Health and Nutrition Examination Survey (NHANES). [28–30] Each study found a positive, but not necessarily linear, relationship between the two. [28–30] Compared to other inflammatory markers (e.g., platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and neutrophil-to-lymphocyte ratio), Xu et al [30] identify SII as a superior marker that could potentially be used as a warning for early identification of personal inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were originally developed to predict survival and cancer recurrence [ 15 , 16 ]. Further studies indicated that elevated SII and SIRI values are prognostic indicators of poor clinical outcomes not only in cancers but also in numerous other diseases, including cardiovascular and cerebrovascular conditions [ 17 19 ]. Nonetheless, research into the associations of the SII and SIRI with mortality risk in OA patients is lacking.…”
Section: Introductionmentioning
confidence: 99%